Semi-solid electrolyte and sodium ion battery

By using semi-solid electrolyte with organic/inorganic composite three-dimensional framework in sodium ion batteries, the safety hazards of liquid electrolytes and the insufficient performance of solid electrolytes are solved, and the effects of high safety and long cycle life are achieved, while simplifying the preparation Process and reduce costs.

CN117352830BActive Publication Date: 2025-02-18ZHANGJIAGANG GUOTAI HUARONG NEW CHEM MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210735579.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-27
Publication Date
2025-02-18
Estimated Expiration
2042-06-27

AI Technical Summary

Technical Problem

In existing sodium ion batteries, the flash point of liquid electrolytes is low, flammable and easy to leak, which poses safety hazards. At the same time, the low room temperature conductivity and poor interface compatibility of solid electrolytes restrict their development.

Method used

An organic/inorganic composite three-dimensional framework is used as the basis for the semi-solid electrolyte, and an electrolyte with excellent conductivity and safety performance is formed by combining polymer A, sodium salt A and inorganic ceramics. The electrolyte is polymerized in situ by polymer monomer under the presence of an organic/inorganic composite three-dimensional framework, a thermal initiator and a liquid electrolyte to form a semi-solid electrolyte.

Benefits of technology

It achieves the improvement of the circulation performance and cycle life of sodium ion batteries while maintaining high safety, and simplifies the preparation process and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to a semi-solid electrolyte and a sodium ion battery. In order to solve the problem that sodium ion batteries in the prior art cannot take into account both safety and cycle performance, the present invention provides a semi-solid electrolyte, including an organic / inorganic composite three-dimensional skeleton, a polymer monomer, a thermal initiator and a liquid electrolyte, wherein the organic / inorganic composite three-dimensional skeleton includes a polymer, a sodium salt and an inorganic ceramic, the polymer monomer is vinylene carbonate, the thermal initiator is azobisisobutyronitrile, and the liquid electrolyte includes an organic solvent, a sodium salt and a functional additive. The semi-solid electrolyte of the present invention can significantly improve battery safety and room temperature and high temperature cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium batteries, and in particular relates to a semi-solid electrolyte and a sodium ion battery. Background Art

[0002] Lithium secondary batteries have been widely used in many fields due to their high energy density, long cycle life and environmental friendliness. However, factors such as limited lithium resources and high prices restrict the further development of sodium-ion batteries. Sodium-ion batteries are gradually replacing sodium-ion batteries in the market due to their low raw material prices, sufficient reserves, and consistent production processes.

[0003] Commercial sodium-ion batteries generally use liquid electrolytes, which have a low flash point, are flammable and easy to leak, and have potential safety hazards. Replacing liquid electrolytes with solid electrolytes can fundamentally solve the safety problems of sodium-ion batteries. However, the low room temperature conductivity and poor interface compatibility of solid electrolytes restrict the development of solid-state sodium-ion batteries. Semi-solid electrolytes are a form between solid and liquid, which can improve the safety performance of batteries, improve ion transmission performance, and achieve longer cycle life.

[0004] Patent application CN112290081A discloses a method for preparing a high-energy-density quasi-solid electrolyte. After pre-sodiumized polyphenylene sulfide powder and polytetrafluoroethylene powder are oriented and drawn, a pre-sodiumized polyphenylene sulfide solid electrolyte membrane is made, and then bonded with a polyethylene film to form a sodium ion polyethylene-polyphenylene sulfide-based composite solid electrolyte. This patent can increase the number of sodium ion migration and achieve battery flame retardancy. However, this patent needs to be carried out in multiple steps when preparing the quasi-solid electrolyte, and PTFE oriented drawing equipment needs to be used. The preparation method is relatively complicated and energy-intensive, and practice has shown that it cannot be implemented on a large scale in battery manufacturing.

[0005] Patent application CN112993391A discloses a method for preparing a quasi-solid electrolyte, which is composed of sodium salt, organic solvent, polymer monomer and photocuring initiator. The prepared electrolyte has excellent ionic conductivity and voltage window. However, the three-dimensional skeleton substrate used in the patent is glass fiber, which can only play a partition role in the battery system and has no effect on battery performance or even deteriorates it. Summary of the invention

[0006] The purpose of the present invention is to provide an organic / inorganic composite three-dimensional framework capable of improving the cycle performance of a semi-solid sodium ion battery.

[0007] Another object of the present invention is to provide a semi-solid electrolyte which has certain practical prospects and has a longer cycle life while having high safety.

[0008] Another object of the present invention is to provide a semi-solid sodium ion battery that has both high safety and long cycle life and has a simple preparation process and low cost.

[0009] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0010] An organic / inorganic composite three-dimensional skeleton, the organic / inorganic composite three-dimensional skeleton is used for a semi-solid electrolyte, the raw materials of the organic / inorganic composite three-dimensional skeleton include polymer A, sodium salt A and inorganic ceramics, the polymer A is poly(vinylidene fluoride-co-hexafluoropropylene), and the sodium salt A is one or more of sodium hexafluorophosphate, sodium bis(trifluoromethylsulfonyl)imide and sodium bis(fluorosulfonyl)imide.

[0011] Preferably, the mass ratio of the polymer A, the sodium salt A and the inorganic ceramic is 1:(0.4-1.4):(0.01-0.15).

[0012] Further preferably, the mass ratio of the polymer A, the sodium salt A and the inorganic ceramic is 1:(0.7-1.2):(0.05-0.12).

[0013] Still more preferably, the mass ratio of the polymer A, the sodium salt A and the inorganic ceramic is 1:(0.9-1.1):(0.07-0.11).

[0014] Preferably, the inorganic ceramic is Na3Zr2Si2PO 12 (NZSPO).

[0015] A method for preparing the organic / inorganic composite three-dimensional skeleton comprises mixing the polymer A, the sodium salt A and the inorganic ceramic with an organic solvent A to form a slurry, and then drying the slurry to form a film, which is the organic / inorganic composite three-dimensional skeleton.

[0016] Preferably, the organic solvent A is acetone and / or tetrahydrofuran.

[0017] Preferably, the mass ratio of the organic solvent A to the polymer A is (5-10):1.

[0018] Further preferably, the mass ratio of the organic solvent A to the polymer A is (5.5-8):1.

[0019] Still more preferably, the mass ratio of the organic solvent A to the polymer A is (5.8-7):1.

[0020] A semi-solid electrolyte, polymer monomers are in situ polymerized in the presence of an organic / inorganic composite three-dimensional skeleton, a thermal initiator and a liquid electrolyte to form the semi-solid electrolyte, and the organic / inorganic composite three-dimensional skeleton is the above-mentioned organic / inorganic composite three-dimensional skeleton.

[0021] Preferably, the mass ratio of the organic / inorganic composite three-dimensional skeleton, polymer monomer, thermal initiator and liquid electrolyte is 1:(0.118-0.278):(0.005-0.014):(0.352-0.833).

[0022] Preferably, the mass ratio of the organic / inorganic composite three-dimensional skeleton, polymer monomer, thermal initiator and liquid electrolyte is 1:(0.138-0.214):(0.007-0.011):(0.414-0.639).

[0023] Further preferably, the mass ratio of the organic / inorganic composite three-dimensional skeleton, polymer monomer, thermal initiator and liquid electrolyte is 1:(0.15-0.175):(0.007-0.009):(0.45-0.525).

[0024] Preferably, the polymer monomer is vinylene carbonate.

[0025] Preferably, the thermal initiator is azobisisobutyronitrile.

[0026] Preferably, the liquid electrolyte comprises an organic solvent B, a sodium salt B and a functional additive.

[0027] Preferably, the mass ratio of the organic solvent B, the sodium salt B and the functional additive is (1.8-8):0.42:(0.01-0.18).

[0028] Further preferably, the mass ratio of the organic solvent B, the sodium salt B and the functional additive is (2.3-5.5):0.42:(0.012-0.0.15).

[0029] Still more preferably, the mass ratio of the organic solvent B, the sodium salt B and the functional additive is (2.7-4.5):0.42:(0.015-0.13).

[0030] Preferably, the organic solvent B is a mixture of cyclic carbonate and chain carbonate.

[0031] Further preferably, the mass ratio of the cyclic carbonate to the linear carbonate is 1:(1.3-6.5).

[0032] Still more preferably, the mass ratio of the cyclic carbonate to the linear carbonate is 1:(1.5-4.7).

[0033] Preferably, the cyclic carbonate comprises ethylene carbonate or a mixture of ethylene carbonate and propylene carbonate.

[0034] Preferably, the linear carbonate includes one or more of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.

[0035] According to the invention, the sodium salt B is one or more of sodium hexafluorophosphate, sodium bis(trifluoromethylsulfonyl)imide and sodium bis(fluorosulfonyl)imide.

[0036] Preferably, the sodium salt A and the sodium salt B are of the same type.

[0037] Preferably, the functional additive is vinyl sulfate and / or methylene methane disulfonate.

[0038] A method for preparing the sodium ion battery comprises the steps of uniformly mixing the polymer monomer, the thermal initiator and the liquid electrolyte and injecting the mixture into the battery to obtain the sodium ion battery through in-situ polymerization.

[0039] Preferably, the temperature of the in-situ polymerization is 50-80°C, more preferably 55-65°C.

[0040] Preferably, the in-situ polymerization time is 4-15 hours, more preferably 8-12 hours.

[0041] Preferably, during the in-situ polymerization process, a pressure of 200-300KG is applied to the battery, more preferably 220-280KG.

[0042] Preferably, the battery is left to stand for 1-3 days before the in-situ polymerization.

[0043] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0044] 1. The present invention is compatible with the existing battery manufacturing process, is relatively simple and convenient to prepare, and has certain practical prospects.

[0045] 2. The present invention can have excellent cycle performance while having high safety. DETAILED DESCRIPTION

[0046] The present invention is further described below in conjunction with the examples. However, the present invention is not limited to the following examples. The implementation conditions used in the examples can be further adjusted according to the different requirements of specific use, and the implementation conditions not specified are conventional conditions in the industry. The technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.

[0047] The preparation methods of the semi-solid electrolytes reported so far are relatively complicated and their performance in full-battery applications is relatively poor. In order to promote large-scale commercial use, their electrochemical performance and safety performance need to be further improved.

[0048] In view of the deficiencies in the prior art, the inventors of this case have proposed the technical solution of the present invention after long-term research and extensive practice. The present invention assembles an organic / inorganic composite three-dimensional skeleton with positive and negative electrode plates into a full battery, optimizes the liquid electrolyte formula, and directly injects the polymer monomer, cross-linking agent, thermal initiator and liquid electrolyte into the above battery after simple mixing, and obtains a semi-solid sodium ion battery after in-situ curing. The prepared sodium ion battery has excellent room temperature and high temperature cycle performance, and can pass the needle puncture test, and has good safety performance.

[0049] The technical solution, its implementation process and principle will be further explained as follows.

[0050] Example 1

[0051] [positive electrode]

[0052] Weigh the positive electrode material sodium vanadium phosphate, the conductive agent acetylene black and the binder PVDF in a mass ratio of 90:5:5, add an appropriate amount of N-methylpyrrolidone, mix evenly, and prepare the positive electrode slurry. Spread the positive electrode slurry on aluminum foil, roll and cut it after drying to obtain the positive electrode sheet.

[0053] [negative electrode]

[0054] Weigh hard carbon, carbon black, carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 90:5:4.5:0.5, add an appropriate amount of deionized water, stir thoroughly, and obtain a negative electrode slurry. Spread the negative electrode slurry on aluminum foil, roll and cut it after drying to obtain a negative electrode sheet.

[0055] [Organic / inorganic composite three-dimensional framework]

[0056] Poly(vinylidene fluoride-co-hexafluoropropylene), sodium bis(fluorosulfonyl)imide, NZSPO and acetone / tetrahydrofuran mixed solution (mass ratio 1:1) were evenly mixed in a mass ratio of 1:1:0.1:6, and then cast on a glass or polytetrafluoroethylene substrate by solution casting. After drying at room temperature for 12 hours, it was dried in a vacuum drying oven at 50°C for 8 hours, and then demolded and cut.

[0057] [Liquid electrolyte]

[0058] Dimethyl carbonate, ethylene carbonate, ethyl methyl carbonate, sodium bis(fluorosulfonyl)imide, vinyl sulfate and methylene methanedisulfonate in a mass ratio of 1:1:1:0.42:0.034:0.034 were weighed and mixed evenly to obtain a liquid electrolyte.

[0059] [Battery manufacturing]

[0060] The positive electrode, negative electrode and organic / inorganic composite three-dimensional skeleton are used to manufacture and assemble a soft-pack battery with a designed capacity of 110 mAh by adopting a lamination process.

[0061] According to the mass ratio of organic / inorganic composite three-dimensional skeleton, vinylene carbonate, azobisisobutyronitrile and liquid electrolyte being 1: 0.16: 0.008: 0.48, vinylene carbonate, azobisisobutyronitrile and liquid electrolyte were weighed, mixed evenly and then injected into the battery.

[0062] After the battery is filled and sealed, it is left to stand for 36 hours to ensure that the organic / inorganic composite three-dimensional skeleton is completely absorbed and the positive and negative pole pieces are completely soaked. Then, a pressure of 250KG is applied to the battery and placed in a 60℃ environment for 10 hours.

[0063] [Liquid absorption rate]

[0064] Liquid absorption rate = [(mass of the three-dimensional skeleton until saturated with liquid - mass of the three-dimensional skeleton) / (mass of the three-dimensional skeleton)] × 100%.

[0065] [Battery performance test]

[0066] The battery charge and discharge test was conducted at 25°C and 45°C, with a voltage range of 2.75-4.2V. The battery was charged and discharged at a rate of 0.5C, and the capacity retention rate after 200 cycles was tested. Capacity retention rate (%) = (discharge capacity after 200 cycles / discharge capacity after the first cycle) × 100%.

[0067] [Acupuncture test conditions]

[0068] A 10mm diameter steel needle was inserted into the battery at a speed of 3mm / s and stayed inside the battery for 10 minutes to observe the phenomenon and record video.

[0069] Example 2

[0070] It is basically the same as Example 1, except that:

[0071] The sodium bis(fluorosulfonyl)imide in the manufacturing process of the organic / inorganic composite three-dimensional framework and liquid electrolyte is replaced by sodium hexafluorophosphate.

[0072] Example 3

[0073] It is basically the same as Example 1, except that:

[0074] The sodium bis(fluorosulfonyl)imide in the manufacturing process of the organic / inorganic composite three-dimensional framework and the liquid electrolyte is replaced by sodium bis(trifluoromethylsulfonyl)imide.

[0075] Example 4-17 and Comparative Example 4-5

[0076] The method is basically the same as Example 1, except that the component ratio of the liquid electrolyte is as shown in the following table:

[0077] Table 1 Liquid electrolyte component ratios of Example 1, Examples 4-17 and Comparative Examples 4-5

[0078]

[0079]

[0080] Solvent B is a mixed solution of dimethyl carbonate, ethylene carbonate and ethyl methyl carbonate in a mass ratio of 1:1:1; sodium salt B is sodium bis(fluorosulfonyl)imide; “ / ” means not used.

[0081] Comparative Example 1

[0082] The positive electrode sheet, the negative electrode sheet and the organic / inorganic composite three-dimensional skeleton described in Example 1 are directly assembled into a soft-pack battery, and the electrochemical performance test is carried out.

[0083] Comparative Example 2

[0084] When manufacturing the battery, the organic / inorganic composite three-dimensional skeleton is replaced with a glass fiber separator, and the battery is directly assembled with the positive and negative electrodes. Then, vinylene carbonate, azobisisobutyronitrile and liquid electrolyte are weighed in a mass ratio of 1:0.05:3, mixed evenly and injected into the battery.

[0085] Comparative Example 3

[0086] When manufacturing the battery, the organic / inorganic composite three-dimensional skeleton is replaced with a glass fiber separator, and the battery is directly assembled with the positive and negative electrodes. Subsequently, the liquid electrolyte in Example 1 is directly injected into the battery.

[0087] Table 2 Performance test results of Examples 1-17 and Comparative Examples 1-5

[0088]

[0089]

[0090] From the comparison between the embodiment and the comparative example, it can be seen that the liquid absorption rate of the prepared organic / inorganic composite three-dimensional skeleton is about 65%. Although the battery using semi-solid electrolyte is slightly inferior to the battery using liquid electrolyte in terms of cycle performance, it can pass the needle puncture test and has good safety.

[0091] From the comparison between Examples 1-17 and Comparative Examples 1-2, it can be seen that a single organic / inorganic composite three-dimensional framework or in-situ polymerized electrolyte cannot effectively transport sodium ions and cannot exert a better cycle performance. However, the simultaneous introduction of an organic / inorganic composite three-dimensional framework and an in-situ polymerized electrolyte can exert a synergistic effect and improve the cycle performance of a semi-solid sodium ion battery.

[0092] From the comparison between Examples 1-17 and Comparative Examples 4-5, it can be seen that by further optimizing the liquid electrolyte components and introducing an appropriate amount of functional additives, the room temperature and high temperature cycle performance of the semi-solid sodium ion battery can be significantly improved.

[0093] The above description shows that the use of the semi-solid electrolyte of the present application can significantly improve the safety performance of sodium ion batteries; by further optimizing the liquid electrolyte components and adding an appropriate amount of functional additives, a synergistic effect can be exerted to further improve the room temperature and high temperature cycle performance of semi-solid sodium ion batteries.

[0094] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A semi-solid electrolyte, characterized in that: The polymer monomer is in situ polymerized in the presence of an organic / inorganic composite three-dimensional skeleton, a thermal initiator and a liquid electrolyte to form the semi-solid electrolyte. The raw materials of the organic / inorganic composite three-dimensional skeleton include polymer A, sodium salt A and inorganic ceramics. The polymer A is poly(vinylidene fluoride-co-hexafluoropropylene), the sodium salt A is one or more of sodium hexafluorophosphate, sodium bis(trifluoromethylsulfonyl)imide and sodium bis(fluorosulfonyl)imide, the mass ratio of the polymer A, sodium salt A and inorganic ceramics is 1:(0.4-1.4):(0.01-0.15), and the inorganic ceramics is Na3Zr2Si2PO4 12 , the polymer monomer is vinylene carbonate, the liquid electrolyte comprises an organic solvent B, a sodium salt B and a functional additive, the mass ratio of the organic solvent B, the sodium salt B and the functional additive is (1.8-8):0.42:(0.01-0.18), the organic solvent B is a mixture of cyclic carbonates and chain carbonates; the mass ratio of the cyclic carbonates and chain carbonates is 1:(1.3-6.5), the sodium salt B is one or more of sodium hexafluorophosphate, sodium bis(trifluoromethylsulfonyl)imide and sodium bis(fluorosulfonyl)imide, the functional additive is vinyl sulfate and / or methylene disulfonate, and the mass ratio of the organic / inorganic composite three-dimensional skeleton, the polymer monomer, the thermal initiator and the liquid electrolyte is 1:(0.118-0.278):(0.005-0.014):(0.352-0.833).

2. The semi-solid electrolyte according to claim 1, characterized in that The polymer A, the sodium salt A and the inorganic ceramic are mixed with the organic solvent A to form a slurry, and then the slurry is dried to form a film, which is the organic / inorganic composite three-dimensional skeleton.

3. The semi-solid electrolyte according to claim 2, characterized in that The organic solvent A is acetone and / or tetrahydrofuran; And / or, the mass ratio of the organic solvent A to the polymer A is (5-10):

1.

4. The semi-solid electrolyte according to claim 1, characterized in that The thermal initiator is azobisisobutyronitrile.

5. The semi-solid electrolyte according to claim 1, characterized in that The cyclic carbonate includes ethylene carbonate and / or propylene carbonate; And / or, the linear carbonate includes one or more of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.

6. The semi-solid electrolyte according to claim 1, characterized in that The sodium salt B is of the same type as the sodium salt A.

7. A sodium ion battery comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: The electrolyte is the semi-solid electrolyte according to any one of claims 1 to 6.

8. The sodium ion battery according to claim 7, characterized in that: The active material of the positive electrode is sodium vanadium phosphate; the active material of the negative electrode is hard carbon material or metallic sodium.

9. A method for preparing a sodium ion battery as claimed in claim 8, characterized in that: The organic / inorganic composite three-dimensional skeleton is assembled with the positive electrode and the negative electrode into a battery, and then the polymer monomer, thermal initiator and liquid electrolyte are mixed evenly and injected into the battery to obtain the sodium ion battery through in-situ polymerization.

10. The preparation method according to claim 9, characterized in that: The temperature of the in-situ polymerization is 50-80° C.; the time of the in-situ polymerization is 4-15 hours; and the battery is left to stand for 1-3 days before the in-situ polymerization.

Citation Information

Patent Citations

  • Manufacturing method of high-energy-density quasi-solid-state sodium ion battery

    CN112290081A

  • Preparation method and application of quasi-solid electrolyte

    CN112993391A

  • Organic / inorganic composite electrolyte membrane for solid-state sodium ion battery, preparation and application thereof

    CN111628213A